Patient-derived malignant pleural mesothelioma cell cultures: a tool to advance biomarker-driven treatments - Kanellakis, NI; Asciak, R; Hamid, MA; Yao, X; McCole, M; McGowan, S; Seraia, E; Hatch, S; Hallifax, RJ; Mercer, RM; Bedawi, EO; Jones, S; et al. (BMJ Publishing Group, 2020)
Malignant pleural mesothelioma (MPM) is an aggressive cancer, associated with poor prognosis. We assessed the feasibility of patient-derived cell cultures to serve as an ex vivo model of MPM. Patient-derived MPM cell cultures (n=16) exhibited stemness features and reflected intratumour and interpatient heterogeneity. A subset of the cells were subjected to high-throughput drug screening and coculture assays with cancer-specific cytotoxic T cells and showed diverse responses. Some of the biphasic MPM cells were capable of processing and presenting the neoantigen SSX-2 endogenously. In conclusion, patient-derived MPM cell cultures are a promising and faithful ex vivo model of MPM.